Screening of superior genotypes of ailanthus triphysa (Dennst.) Alston. (Matti) for Matchwood quality - Jagaddish Kumar Das (Department of Forest Products and Utilization, College of Forestry, 2018)
A study entitled “Screening of superior genotypes of Ailanthus triphysa (Dennst.) Alston. (Matti) for matchwood quality” was conducted in the College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period, 2016-2018. The objectives were to assess the variation in growth and wood traits of Ailanthus triphysa grown in the main campus of Kerala Agricultural University, Vellanikkara under a tree improvement trial. It was also aimed at selecting the superior genotype in this population through an assessment of the genetic worth of their parents. Among the five best performing progenies, FCV AT 11 and FCV AT 20 were found to perform well in terms of height and collar diameter. The progenies of FCV AT 11 also showed highest mean stem volume of 0.006 m3. Overall mode for number of branches was found to be zero, only one progeny (FCV AT 3) had single branching habit. Regarding bole straightness all the progenies scored 3 “almost straight with 1 or 2 small bends” except progeny of FCV AT 8 and 14 CPTs scored two “slightly crooked with 2 small bends or less than 2 serious bends”. At this stage of the trial, majority of the progenies had good branching habit and bole straightness. This aspect should be utilized in breeding programme so that it will be helpful to improve the tree form, which ultimately upgrade the quality and economic value of the timber. Average survival percentage of the progenies were found to be 94.98 %. The average basic density of CPTs was found to be 0.37 g cm-3, which shows that the wood belongs to the light wood category. Wood colour and grain pattern studies revealed that, single colour (pale yellow) and straight grain pattern was found in all the CPTs respectively. Fibre morphology, vessel morphology, and ray morphology exhibited significant variation among the CPTs whereas, the variation in tissue proportion was found to be non-significant. Pest incidence was found to be one of the major hindrances to the growth of the species. Bioassay using Bacillus thuringiensis (Bt) was found to be effective against both the lepidopteran defoliators, Eligma narcissus (Cram.) and Atteva fabriciella Swederus. In case of E. narcissus, median lethal dose (LD50) was achieved with 10 % concentration of Bt whereas in A. fabriciella, 2.5% Bt concentration was found to be effective. Neem oil showed a clear antifeedant activity against E. narcissus, the feeding rate was reduced to 3.58 % in 2 % neem oil treated leaves as compared to 30.91 % in control. Scoring of pest incidence was found to be non109 significant among the progenies, all the progenies affected moderately by both E. narcissus and A. fabriciella. Ten CPTs namely FCV AT 1, 2, 3, 5, 6, 8, 9, 11, 13, 20 were found to be good combiners for both height and collar diameter. The CPTs with positive GCA could be potentially included in a seed production programme and for further breeding. Broad sense heritability (H2) for height was found to be 0.03 and for collar diameter, 0.1. It could therefore be concluded that height and collar diameter were highly influenced byenvironmental factors rather than genetic factors.